Leadership for Adult and Continuing Education - Jean E. A. Fleming; Rosemary S. Caffarella (Adult Education Research Conference, 2000)
This paper reviews findings from a study of the perceptions of adult educators of leadership for the field of adult and continuing education. Findings are ultimately organized according to the contexts and dimensions of leadership.